(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article gives a brief description of Amorpha Fruticosa L, one of the medicinal plants, and its importance in pharmaceutical use. Amorpha Fruticosa is an introduced species in Uzbekistan, this plant is grown and researched in all regions of our republic as a decorative and medicinal plant.